Training future generations to deliver evidence‐based conservation and ecosystem management. Issue 1 (25th January 2021) - Downey, Harriet; Amano, Tatsuya; Cadotte, Marc; Cook, Carly N.; Cooke, Steven J.; Haddaway, Neal R.; Jones, Julia P. G.; Littlewood, Nick; Walsh, Jessica C.; Abrahams, Mark I.; Adum, Gilbert; Akasaka, Munemitsu; et al.
Abstract: 1. To be effective, the next generation of conservation practitioners and managers need to be critical thinkers with a deep understanding of how to make evidence‐based decisions and of the value of evidence synthesis. 2. If, as educators, we do not make these priorities a core part of what we teach, we are failing to prepare our students to make an effective contribution to conservation practice. 3. To help overcome this problem we have created open access online teaching materials in multiple languages that are stored in Applied Ecology Resources. So far, 117 educators from 23 countries have acknowledged the importance of this and are already teaching or about to teach skills in appraising or using evidence in conservation decision‐making. This includes 145 undergraduate, postgraduate or professional development courses. 4. We call for wider teaching of the tools and skills that facilitate evidence‐based conservation and also suggest that providing online teaching materials in multiple languages could be beneficial for improving global understanding of other subject areas. Abstract : To be effective, the next generation of conservation practitioners and managers need to be critical thinkers and understand how to make evidence‐based decisions. As educators, we should make these a core part of what we teach to prepare our students to make an effective contribution to conservation practice. To help, we have created open access online teaching materials in multiple languages that are stored in Applied Ecology Resources. Resumen: 1. Para ser eficaces, la próxima generación de practicantes y administradores de la conservación deben ser pensadores críticos, con un entendimiento profundo de cómo tomar decisiones basadas en la evidencia y del valor de la síntesis de la misma. 2. Si, como educadores, no hacemos de estas prioridades la parte central de lo que enseñamos, estamos fallando en preparar a nuestros estudiantes para hace una contribución efectiva a la práctica de la conservación. 3. Para ayudar a superar este problema, hemos creado materiales didácticos en línea de acceso abierto en varios idiomas, que serán almacenados en "Applied Ecology Resources". Hasta ahora, 117 educadores de 23 países han reconocido la importancia de esto y ya están enseñando o están por enseñar habilidades para valorar o usar evidencia en la toma de decisiones de conservación. Esto incluye 145 cursos de pregrado, posgrado o cursos de desarrollo profesional. 4. Hacemos un llamado por una amplia enseñanza de las herramientas y habilidades que facilitan la conservación basada en la evidencia y también sugerimos que proporcionar materiales de enseñanza en línea en multiples idiomas podría ser beneficioso para mejorar la comprensión global de otras áreas temáticas. Zusammenfassung: 1. Zum effektiven Handeln brauchen wir in der nächsten Generation von Naturschützern und Naturschutzmanagern kritische Denker mit einem grundlegenden Verständnis von evidenz‐basierten Entscheidungen und dem Wert von Evidenz‐Synthesen. 2. Wenn wir als Dozenten diese Aspekte nicht zu einem zentralen Bestandteil unserer Lehre machen, bereiten wir unsere Studierenden nur unzureichend darauf vor, wirksam zur zukünftigen Naturschutzpraxis beitragen zu können. 3. Um diese Aufgabe zentral anzugehen, haben wir Open‐Access‐Online‐Unterrichtsmaterialien in mehreren Sprachen erstellt, die in den ‚Applied Ecology Resources' gespeichert sind. Bisher haben mindestens 117 Dozenten aus 23 Ländern die Bedeutung dieses Themas erkannt und es entsprechend schon in ihre Lehre eingebaut beziehungsweise sind derzeit dabei, Ihren Studierenden die Möglichkeiten der Bewertung und Verwendung von direkten Belegen bei der Entscheidungsfindung im Naturschutz zu vermitteln. Diese Lehre umfasst 145 Kurse ‐ sowohl auf Bachelor und MSc/PhD‐Ebene wie auch Kurse zur beruflichen Weiterbildung. 4. Wir empfehlen für die Zukunft eine noch umfassendere Vermittlung der Instrumente und Fähigkeiten, die einem evidenzbasierten Naturschutz zugrunde liegen. Darüber hinaus stellen wir die Vorteile einer Bereitstellung von mehrsprachigen Online‐Unterrichtsmaterialien für eine bessere globale Wissensvermittlung auch für andere Fachbereiche heraus 抽象: エビデンスに基づいた保全と生態系管理を促進するための次世代教育 1. 生物多様性をより効果的に保全していくために、次世代の実務者はエビデンスに基づいた意思決定の方法とエビデンスを統合することの価値を深く理解し、また批判的な思考を備える必要がある。 2. 生物多様性保全に関する教育課程においてこの課題を取り扱わなければ、現在の学生が今後の保全活動に対して効果的な貢献を行うようにはならないだろう。 3. この問題を解決するために、本稿ではエビデンスに基づいた保全についてのオープンアクセス・オンライン教材を多言語で作成し、それらをApplied Ecology Resourcesに収蔵した。これまでに、23カ国、145の学部・大学院教育、また専門的能力の開発コースに携わる117人がこの問題の重要性について同意し、保全に関する意思決定におけるエビデンスの評価や利用の技能についての講義を既に行っているか、これから行おうとしている。 4. エビデンスに基づいた保全を促進する手段や技能をより広く教育していくことは今後益々必要となるだろう。また、我々の取り組みのようにオンライン教材を多言語で提供することで、他の研究分野でも世界的な理解の向上を図ることができると考える。 Abstract : 1. 要使得有效, 下一代自然保育執業者及管理人員必須懂得嚴謹的思考, 而且對循證決策及綜合證據的價值有深刻瞭解。 2. 作為自然保育領域的教育者, 如果我們沒有將這些要點放在我們所教學內容的核心, 我們就將會失敗, 不能夠給學生一個好的準備讓他們在自然保育實務上做出有效的貢獻。 3. 為了幫助解決這個問題, 我們創建了開放使用的多語言網上教材。這些教材存儲在 Applied Ecology Resources《應用生態學資料庫》。迄今為止, 來自23個國家的117名教育者已認同這一方面的重要性, 他們並且已經或即將教導學生怎樣在自然保育決策中嚴格評估及利用證據的技能。這包括145門本科, 研究生或專業發展課程。 4. 我們呼籲需要更廣泛地進行循證自然保育相關的工具及技能教育, 並認為需要更多有心人士提供多語言網上教材, 幫助提高各個知識領域的環球理解。 Resumo: 1. Para ser eficaz, a próxima geração de conservacionistas e gestores de vida selvagem tem de ter a capacidade de desenvolver pensamento crítico e deve possuir um conhecimento profundo sobre como tomar decisões com base em evidência, entendendo também o valor de sintetizar a mesma. 2. Se, como educadores, não fazemos destas prioridades uma parte nuclear do que leccionamos, estaremos a falhar na preparação dos nossos estudantes, impossibilitando‐os de realizar uma contribuição efectiva na prática da conservação de natureza. 3. Para ajudar a ultrapassar este problema criámos materiais de ensino on‐line, com acesso aberto e em várias línguas, disponíveis em "Applied Ecology Resources". Até à data, 117 educadores de 23 países reconheceram a importância deste processo e já leccionam, ou estão prestes a fazê‐lo, ensinando como avaliar ou usar evidências na tomada de decisões, aplicadas à conservação da natureza. Aqui se incluem 145 unidades curriculares do primeiro e segundo ciclos do ensino superior, bem como cursos de desenvolvimento profissional. 4. Apelamos à expansão do ensino de ferramentas e competências que facilitem a tomada de decisão na área da conservação da natureza com base em evidência e sugerimos que distribuir material de ensino online em múltiplas línguas, poderá ser também benéfico no sentido de melhorar a compreensão global noutras áreas de conhecimento. Abstrait: 1. Pour être efficace, la prochaine génération de praticiens et de gestionnaires de la conservation doit être des penseurs critiques ayant une compréhension approfondie de la manière de prendre des décisions fondées sur des preuves et de la valeur de la synthèse de preuves. 2. Si, en tant qu'éducateurs, nous ne faisons pas de ces priorités un élément central de ce que nous enseignons, nous ne préparons pas nos élèves à apporter une contribution efficace à la conservation de la nature. 3. Pour aider à surmonter ce problème, nous avons créé du matériel pédagogique en ligne en libre accès dans plusieurs langues qui est stocké sur le site internet Applied Ecology Resources. Jusqu'à présent, 117 éducateurs de 23 pays ont reconnu son importance et enseignent déjà ou sont sur le point d'enseigner des compétences en matière d'évaluation ou d'utilisation des preuves dans la prise de décision en matière de conservation. Cela comprend 145 cours de premier cycle, de troisième cycle ou de perfectionnement professionnel. 4. Nous appelons à un enseignement plus large des outils et des compétences qui facilitent la conservation fondée sur des preuves et suggérons également que la fourniture de matériel didactique en ligne dans plusieurs langues pourrait être bénéfique pour améliorer la compréhension globale d'autres domaines.